The nature of the request for grace of private initiatives - Paz Sime, Miguel Angel (2018)
In the present work, the author analyzes the scope of the classification of private initiatives as requests for grace with respect to the rights of the proponents within the framework of the relevant legislation. To do this, he initially develops the concepts that legislation, jurisprudence and doctrine give us on the request for grace and on private initiatives, focusing then on commenting on the limitations of current regulations on them, and the correct reading that should be given in search of harmonization with the constitutional right of petition and with the principles of due administrative procedure.